Bibliometrics Analysis and Research Profiling to Solve User Experience Overload Information - Wahyu Andhyka Kusuma; Azrul Hazri bin Jantan; Rusli bin Abdullah; Novia Indriaty Admodisastro; Noris binti Mohd Norowi; Evi Dwi Wahyuni; Siti Alfiyatun Ni’mah (Universitas Muhammadiyah Malang, 2022)
Today's technology is not just a tool to help humans perform complex tasks but has an impact on the revolutionary changes in human thought and behavior as well as culture and societal civilization that we need to know and follow, such as the current development of UX design, UX is a type of work-related to how to increase the satisfaction of application users and site visitors seen from the value for benefits, also the pleasure that the user gets from an application or site. UX is also a pattern that requires the industry and researchers to think that the human factor is more than just maintaining the user's functional needs, moreover, UX brings the concept that the user is a user. UX research is needed on the relationship between systems and interactive experiences learning about cross-disciplinary research experiences using large-scale research profiling studies and bibliometric analysis. People who use systems experiences are becoming more and more important, and because of this, interactive technologies are becoming more and more important in these experiences. Research studies show that the number of publications is growing rapidly indicating a growing scientific interest in experiential research.